Challenges in nodal peripheral T-cell lymphomas: from biological advances to clinical applicability - Zain, Jasmine; Kallam, Avyakta (Frontiers in Oncology, 2023)
T cell lymphomas are a heterogenous group with varying biological and clinical features that tend to have poor outcomes with a few exceptions. They account for 10-15% of all non-Hodgkin lymphomas (NHL), and 20% of aggressive NHL. There has been little change in the overall prognosis of T cell lymphomas over the last 2 decades. Most subtypes carry an inferior prognosis when compared to the B cell lymphomas, with a 5-year OS of 30%. Gene expression profiling and other molecular techniques has enabled a deeper understanding of these differences in the various subtypes as reflected in the latest 5th WHO and ICC classification of T cell lymphomas. It is becoming increasingly clear that therapeutic approaches that target specific cellular pathways are needed to improve the clinical outcomes of T cell lymphomas. This review will focus on nodal T cell lymphomas and describe novel treatments and their applicability to the various subtypes.